Is greater decisionmaking power of women associated with reduced gender discrimination in South Asia? - Smith, Lisa C.; Byron, Elizabeth (International Food Policy Research Institute, 2005)
To investigate this issue, the study draws on Demographic and Health Survey data collected during the 1990s in four countries: Bangladesh, India, Nepal, and Pakistan. The main empirical technique employed is multivariate regression analysis with statistical tests for significant differences in effects for girl and boy children. A total of 30,334 women and 33,316 children under three years old are included in the analysis. The study concludes that, for the South Asia region as a whole, an increase in women’s decisionmaking power relative to men’s, if substantial, would be an effective force for reducing discrimination against girl children.